Tinjauan hukum terhadap power purchase agreement (PPA) antara PT Paiton Energy Company dengan Perusahaan Umum Listrik Negara (PLN) - ABDI, Jusra ([Yogyakarta] : Universitas Gadjah Mada, 2009)
In order to fulfill the demand of electricity energy, the Indonesian goverment has negotiated with private consortium. As part of pre-contractual activities, the negotiation resulted in Power Purchase Agreement (PPA) between PT Paiton Energy Company (Paiton) as seller and State Own Electricity Company (PLN) as buyer. This contract has been signed on February 12, 1994 in Jakarta then implemented as Projek Paiton I (Paiton Project I). Therefore, this research focuses on the power purchase agreement signed by PLN and Paiton in the context of legal studies using an analitical prescriptive approach. According to this approach, this research is expected to produce new argumentation, theory and concept as a prescription to overcome to the legal problems. This research analyses documents, bills, regulations and other relevant texts in the legal system of the Republic of Indonesia. This research shows that PLN, which has authority to provide public electricity , has been under pressure and almost powerless in dealing with Paiton. During negotiation proccess, Paiton has conducted communication with the head of government separately hence the government negotiator team's offers were always in comply with Paiton's interest. Having familial relationship and direct access to the head of authoritarian government personally, Paiton has the psychological superiority in the negotiation proccess. This condition has made the agreement between PLN and Paiton to be catogerized as undue influence (willsgebreken).